Clinical and Neurodevelopmental Characteristics of Enterovirus and Parechovirus Meningitis in Neonates - Bucci, Silvia; Coltella, Luana; Martini, Ludovica; Santisi, Alessandra; De Rose, Domenico Umberto; Piccioni, Livia; Campi, Francesca; Ronchetti, Maria Paola; Longo, Daniela; Lucignani, Giulia; Dotta, Andrea; Auriti, Cinzia (Frontiers in Pediatrics, 2022)
Background: Non-polio-enteroviruses (EV) and human parechoviruses (HPeV) are small RNA viruses, which in newborns cause infections with a wide range of severity. Today molecular biology tools allow us to diagnose viral meningitis in neonates, sparing patients from useless antibiotics. Data on neurodevelopmental outcome of children who contract enterovirus meningitis in early childhood are still limited in the literature. Aims: To evaluate the neurodevelopmental outcome of newborns with documented enterovirus and parechovirus meningitis contracted within the first months of life. Methods: Enterovirus and parechovirus were detected on cerebrospinal fluid (CSF) and plasma by RT-PCR. The virological typing was done according to WHO recommendations. During the hospitalization each neonate underwent many diagnostic and instrumental examinations, to evaluate any neurological lesions attributable to the infection. After the discharge children entered in an outpatient interdisciplinary assessment process, comprehensive of the administration of Bayley III scales up to 12 months old. Results: We observed longitudinally 30 children, born at term (mean GA 39.7 ± 0.8 weeks, mean birthweight was 3457 ± 405 grams), who contracted enterovirus and parechovirus meningitis within the first month of life (mean age at diagnosis was 15.8 ± 7.33 days). We were able to perform the genetic typing only on 15/30 (50.0%) cerebrospinal fluid (CSF) samples from 15 neonates. We found MRI anomalies in 9/26 observed neonates (34.6%): one of them presented brainstem abnormality that are specific of enteroviral central nervous system (CNS) involvement. During the follow up children displayed an overall normal neurodevelopment and no deficit in visual and hearing areas. The mean cognitive (105.19 ± 8.71), speech (100.23 ± 8.22) and motor (97.00 ± 8.98) composite scores, assessed by Bayley III, were normal in 29/30 (96.7%). Despite this, children with pathological brain magnetic resonance imaging (MRI) scored significantly lower (p=0.01) than children with normal brain MRI on cognitive subscale at 12 months of life. Conclusions: Early enterovirus infections can be associated to brain MRI abnormalities, more frequently the earlier the infection. Although within a normal range, our children with pathological brain MRI scored significantly lower than those with normal brain MRI on cognitive subscale at 12 months of life.